Perbandingan status gizi dan karies gigi pada murid SD Islam Athirah dan SD Bangkala III Makassar - Nurlindah Hamrun; Mughny Rathi (DiscoverSys Inc., 2009)
Economic status has an impact in life aspect, including nutrition status, caries, andoral hygiene. The aim of this study was to compare the nutritional status, dentalcaries and oral hygiene of Islam Athirah elementary school representing higheconomic status and Bangkala III elementary school, representing low economicstatus. Samples were 120 children of aged 10-11 years. Study design was crosssectional study. The criteria of school chosen, was based on annual tuition fee,contribution fee, entrance school fee, and the presence of school operational aid(Dana BOS). Nutrition status was accessed using Z-score, dental caries using def-tindex, and oral hygiene status accessed using OHI-S (DI-S and CI-S). Data of eatinghabitual, type of food, education and occupation of parents, frequency and method oftooth brushing were obtained from questionnaire. The results of this study showed nosignificant difference of nutritional status and oral hygiene status for both schools(Mann-Whitney, p = 0.281 and 0.936), whereas significant difference was found fordental caries status between Islam Athirah and and Bangkala III elementary school(p=0.01).